2017
DOI: 10.1099/mic.0.000504
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the protein architecture of DNA-binding transcription factors in bacteria and archaea

Abstract: Gene regulation at the transcriptional level is a central process in all organisms where DNA-binding transcription factors play a fundamental role. This class of proteins binds specifically at DNA sequences, activating or repressing gene expression as a function of the cell's metabolic status, operator context and ligand-binding status, among other factors, through the DNA-binding domain (DBD). In addition, TFs may contain partner domains (PaDos), which are involved in ligand binding and protein-protein intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In contrast, 56.3% of the collection do not exhibit a clear correlation with the genome size, suggesting that a large proportion of families have independent evolutionary events associated with their increasing, such as duplications or gene losses, opening questions to be further explored, such as how many families in a genome are product of lateral gene transfer or what occurs with the regulated genes or how many families with a similar distribution pattern across Bacteria and Archaea, are product coevolution processes. In addition, we found a specific association between the DNA-binding domains and their associated companion domains, as it has previously described [3], suggesting that the scaffold to protein-protein interactions could be conserved among members of the same family contacts, as occurs in the Crp family and that their association in diverse bacterial and archaeal genomes could increase the ability of the organisms to recognize and respond to diverse environmental stimuli [30]. This result opens the opportunity to predict and modify the probable ligands to understand the diversity of signals that modulate the activity of transcription factors, as it has been identified for E. coli [31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, 56.3% of the collection do not exhibit a clear correlation with the genome size, suggesting that a large proportion of families have independent evolutionary events associated with their increasing, such as duplications or gene losses, opening questions to be further explored, such as how many families in a genome are product of lateral gene transfer or what occurs with the regulated genes or how many families with a similar distribution pattern across Bacteria and Archaea, are product coevolution processes. In addition, we found a specific association between the DNA-binding domains and their associated companion domains, as it has previously described [3], suggesting that the scaffold to protein-protein interactions could be conserved among members of the same family contacts, as occurs in the Crp family and that their association in diverse bacterial and archaeal genomes could increase the ability of the organisms to recognize and respond to diverse environmental stimuli [30]. This result opens the opportunity to predict and modify the probable ligands to understand the diversity of signals that modulate the activity of transcription factors, as it has been identified for E. coli [31].…”
Section: Discussionsupporting
confidence: 85%
“…activating or repressing gene expression. In general, TFs are two-domain proteins, with a DNA-binding domain (DBD) in either the amino or carboxy terminus, which is involved in specific contacts with the regulatory region of the corresponding cognate genes, and an additional domain associated with diverse functions such as ligand binding or protein-protein interactions [3,4]. To date, diverse studies have shown that some TF families are common to bacteria and archaea, suggesting that the mechanisms affecting gene expression could be similar in the cellular domains of both of these groups of prokaryotes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Homology has been observed between bacterial and archaeal TFs that activate or repress genes in response to environmental stimuli [27,28]. In archaea, these regulatory TFs differ from the general transcription factors (GTFs [29]) required for the initiation of basal transcription, such as TATA-binding protein (TBP) and RNA polymerase, which resemble those of eukaryotes.…”
Section: Tfs Interact Directly With Environmental Signals To Control mentioning
confidence: 99%
“…Archaeal regulatory TFs are enriched for DNA-binding domains that strongly resemble those of bacteria, such as helix-turn-helix domains [28,33]. As in bacteria, the majority of archaeal TFs consist of a DNA-binding domain and a partner domain [27,28]. Nearly 50% of known bacterial partner domains bind to a small molecule, also called an inducer or ligand, that affect DNA-binding affinity [34,35].…”
Section: Tfs Interact Directly With Environmental Signals To Control mentioning
confidence: 99%
See 1 more Smart Citation